Ocorrência, caracterização e eficiência de fungos micorrízicos em Eucalyptus grandis e Acacia mearnsii - Mello, Andréa Hentz de (2006)
It is essential that the quality of seedlings production in the forest species has an appropriate substrate, with good structure, consistency, high porosity, high capacity of nutrition and water retention and inoculated by mycorrhizal fungi. The Eucalyptus grandis and Acacia mearnsii show the capacity to form symbiosis with ectomycorrhizal fungi (fECMs), which help the plant growth by increasing the water and nutritive absorption, that result in prevention of root diseases and survival in diferent environmental conditions. This study was evaluated with the aims: a) to select, to isolate, to multiply and to identify at morphological and/or molecular level the ectomycorrhizal fungi and arbuscular mycorrhizal fungi (FMAs) from quartzipsament soil to using in seedlings inoculation of E. grandis and A . mearnsii; b) to determine the phosphour level that to allow compatibility in increasing of seedlings growing with the maximum mycorrhizal association; and c) to study the stock of phosphour in the seedlings of E. grandis produced in different substrates. The studies were carried out in the Biology and Microbiology Laboratory of Prof. Marcos Rubens Fries, in Soil Science Department, Federal University of Santa Maria, and in greenhouse conditions at Soil Science Department, in the São Francisco de Assis city, Rio Grande do Sul state, in sandy soil. The arbuscular mycorrhizal fungi (FMAs) found in the area were Acaulospora scrobiculata Trappe, Gigaspora margarita Becker & Hall; Glomus clarum Nicolson & Schenck; Glomus etunicatum Becker & Gerdemann; Scutellospora heterogama Nicolson & Gerdemann. The species fECMs found were Pisolithus sp Alb.& Schwein; Scleroderma sp (Person) Fries and Pisolithus microcarpus (Cooke& Mossee) Comm. The Scleroderma sp. UFSMSc1 was studied at morphological and molecular level. The Acacia mearnsii showed mycorrhizal colonization by FMAs in the substrates with high phosphour level, and the species of FMAs most efficient were G. clarum and G. etunicatum. It was characterized this leguminous plant with intermediary mycorrhizal dependence. For the E. grandis, the inoculation with P. microcarpus (UFSC-Pt 116) was efficient for the seedlings production because this isolated could be adapted in less P level added in the substrate. In the field, the seedlings produced with the P. microcarpus UFSC-Pt 116 showed the highest survive, growth in height and diameter in relation to the non-inoculated seedlings. This study proves that the potential of mycorrhizal fungi in the quality of seedlings production of E. grandis and A. mearnsii.